A vote for murder : a novel - Bain, Donald, 1935-2017 (Fletcher, Jessica. Murder, she wrote., 2004)
Jessica's in Washington, D.C., to support a senator's new literacy initiative. The weeklong literacy event includes a visit to the White House to meet the president and a lavish party or two. But during one affair at the senator's home in Virginia, Jessica discovers the dark side of politics...At the foot of a rickety staircase, she finds the body of the senator's chief of staff. Her search for culprits leads her from the shady halls of the Library of Congress to the D.C. social scene and even the FBI.